EVALUATING THE LEVEL OF LAMININ, ADH, AND SOME BIOCHEMICAL VARIABLES IN PEOPLE WITH HYPERTENSION - Muhammad Abdullah Hassan Al-Jubouri; Omar Thaer Jawad; Muhammad Khattab Omar Al-Samarrai (European Science Publishing, 2024)
Abstract: The ongoing study aimed to evaluate the levels of laminin and ADH and a number of biochemical variables in people with high blood pressure. The study collected 90 samples from both sexes, including 60 samples from sick people and 30 from healthy people. Specialised doctors diagnosed the patients. Their ages included (25-70) years. The specimens were collected from the cardiovascular centre in Balid General Hospital Salah Al-Din, hypertensive patients from 1/10/2023 until 20/12/2023. This study evaluates the level of laminin, antidiuretic hormone and some biochemical parameters, including- Lipid profiles (Cholesterol(cho), Triglycerides (TG), Low-density lipoprotein cholesterol (LDL-C), High-density lipoprotein cholesterol (HDL-C) and Very low-density lipoprotein cholesterol (VLDL-C)) and Atherosclerosis content. The results showed that Laminin, Antidiuretic hormone, Total cholesterol, Triglycerides, Low-density lipoprotein cholesterol (LDL-C), Very low-density lipoprotein cholesterol (VLDL-C) and Atherosclerosis content saturation were significantly elevated in the hypertensive patients sample compared with normotensive persons. At the same time, the High-density lipoprotein cholesterol (HDL-C) level shows a significant decrease in hypertensive patients compared with normotensive persons. So, we can conclude that hypertension may affect the laminin level, but ADH, lipid profile and atherosclerosis content increase the blood pressure level.
Keywords: Hypertension disease, Laminin, ADH, lipid profile, Atherosclerosis content.